Stowage Needs in Cars - Holm, Karl-Johan; Lexberg, Erik (My University, 2019)
This Master Thesis was carried out at the Department of Industrial and Materials Science at Chalmers University of Technology in collaboration with CEVT AB. The Master Thesis was carried out by Karl-Johan Holm and Erik Lexberg, two students in the Product Development master program at Chalmers. CEVT is a technology developing company for the Geely Group which means that one part of their operation is to develop cars for the Chinese market. Since CEVT is located in Sweden and the engineers mostly have experience of the European market, a knowledge gap exists towards the user needs in the Chinese market. This Master Thesis aims to reduce this knowledge gap towards user needs for stowage in cars. To do so, a user study including interviews, observations, questionnaire and document analysis was carried out, both in Sweden and in China. The results include a list of 60 items that the Chinese users bring into their cars, the popularity of these items and their preferred placement inside the cars. The results also include a recommendation about changes relating to stowage that has to be done in the car in order to fulfill the user needs. One part of this thesis aimed to investigate how the stowage would be affected in a carsharing situation which also can be found in the result section. One example of solutions needed for carsharing is to have lockable stowage in which the owner of the car can stow their personal belongings when lending it to others. Lastly, a concept was developed in order to present a solution to one of the issues identified in the study. The concept was a rotatable front passenger seat cushion which enables the user to stow heavy items like bags safely in the front row. Thanks to the modular interface on the back of the cushion, the user can stow a variety of items which are difficult to stow in today’s solutions. A few examples of items that are difficult to stow and that can be solved by this concept are: tissue boxes, food and beverage, jackets and purses.